IMPLEMENTASI FLANDERS INTERACTION ANALYSIS CATEGORIES SYSTEM (FIACS) DALAM PENGAJARAN BAHASA INGGRIS DI KELAS TEKNIK KOMPUTER - Masniati Murni Ritonga (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2019)
This research is very important to be carried out considering the crucial role of English for students of Politeknik LP3I Medan. Yet, in this study later, researchers will investigate the model of English teaching lecturers by analyzing the utterances they say to students while teaching. Here the researcher will analyze the utterance by using FIACS (Accept feelings, Praises or encourages, Accepts or uses ideas, Ask questions, Lecturing, Giving direction, Criticizing or justifying authority) to see the types of lecturers' speeches and student responses (students talk response, students talk initiation, Silence or confusion) in teaching and learning activities. Then the researcher will analyze the teaching model applied by the lecturer with other supporting theories. The research method used in this study is a qualitative analysis of the content in which all data will be displayed and analyzed according to the contents of the interaction of students and lecturers when the English learning process takes place and the results of this study will be explained qualitatively. Data will be collected through transcripts from video recordings containing lecturers' teaching dialogues for 1 month and closed interviews. The sample of this study was two English lecturers at the Lp3i Medan Polytechnic Directorate level I & II. Then, the data that has been collected will be analyzed in several stages, such as: transcribing, data displaying, classifying, analyzing, comparing and concluding. The results of this study found that the two lecturers used as samples in this study used all kinds of speech contained in the theory of Flanders 2010 with different portions, but lecturer A was more dominant using the type of questioning, while lecturer B was more dominant giving direction with the same goal namely stimulating students to actively participate in interacting in class using English. Then the researchers found that both in lecture class A and lecture B, students actively interacted both in responding to lecturers and communicating among their peers. It can be concluded that the lecturers use students-centered learning methods to create a communicative classroom atmosphere and familiarize students more with interacting using English and this study also found that computer engineering students whose predominantly male students had kinesthetic characters active so that they are more active when the lecturer stimulates movement and practice. Keywords: qualifications, teaching model, FIACS, Students-centered learning, interaction, implementation.